1987
DOI: 10.1007/bf03189906
|View full text |Cite
|
Sign up to set email alerts
|

Biological N-oxidation of adenine and 9-alkyl derivatives

Abstract: In vitro metabolism of adenine, 9-methyladenine, and 9-benzyladenine using hepatic microsomes of hamster, mouse and rat was investigated. The results indicated that adenine was apparently not susceptible to microsomal N-oxidation. N-oxidation of 9-methyladenine was also not detected, whereas N-demethylation was observed with hepatic microsomes derived from hamster and rat but not from mouse. With 9-benzyladenine, both 1-N-oxide formation and N-debenzylation occurred with microsomes of all species in various am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Reverse-phase HPLC has been used for the separation of aldoximes 45 , ketoximes 46 , amidoximes 14,47 52 and nitrones 3,26,53 55 . This method also served to identify Noxides derived from pyridines 7,29,31,56 63 , pyrimidines 8,9,16 , pyrazines 9 , pyridazines 9 and purines 64,65 ; the latter class of heteroaromatic N-oxides was analyzed on cationic exchange columns.…”
Section: High-performance Liquid Chromatographic (Hplc) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reverse-phase HPLC has been used for the separation of aldoximes 45 , ketoximes 46 , amidoximes 14,47 52 and nitrones 3,26,53 55 . This method also served to identify Noxides derived from pyridines 7,29,31,56 63 , pyrimidines 8,9,16 , pyrazines 9 , pyridazines 9 and purines 64,65 ; the latter class of heteroaromatic N-oxides was analyzed on cationic exchange columns.…”
Section: High-performance Liquid Chromatographic (Hplc) Methodsmentioning
confidence: 99%
“…Studies with the two purines conducted with hepatic preparations from other species revealed increasing rates of 1-N-oxide formation in the order guinea-pig < rat < rabbit < mouse < hamster 64,65 . Similarly, the anticoccidial agent aprinocid, a halogenated congener of 9-benzyladenine, is converted to an active 1-N-oxide by liver microsomes from the chicken and dog 107 .…”
Section: Formation Of N-oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the metabolism -of 9-substitutedadenines showed that they were only coverted to 1-Noxides by a phenobarbital-inducible cytochrome P450 species, presumably CYP2B. This enzyme failed to oxidize adenine to adenine-1-N-oxide (11,12,24). Using rats pretreated with either 3-methylcholanthrene or isosafrole (inducers of CYP1), Clement and Kunze (25) demonstrated that adenine, at high substrate concentrations, was converted to 6-hydroxylaminopurine.…”
Section: Amiphenazolementioning
confidence: 98%
“…The metabolism of many of these compounds has been studied (1-3), and generally it has been observed that compounds used in clinical medicine are not genotoxic and are metabolized by oxidation at one or more nuclear nitrogens (6)(7)(8)(9)(10)(11)(12), whereas those produced by pyrolysis are potent mutagens (13) and are metabolized by N-hydroxylation of the exo amino group (14)(15)(16). This has led to the concept (1-3) that nuclear N-oxidation of aminoazaheterocycles is a detoxication process, whereas N-hydroxylation of the exo amino group is a toxication reaction (Fig.…”
Section: Introductionmentioning
confidence: 99%